2018 IEEE International Symposium on Information Theory (ISIT) 2018
DOI: 10.1109/isit.2018.8437638
|View full text |Cite
|
Sign up to set email alerts
|

Sparsity-based Defense Against Adversarial Attacks on Linear Classifiers

Abstract: Deep neural networks represent the state of the art in machine learning in a growing number of fields, including vision, speech and natural language processing. However, recent work raises important questions about the robustness of such architectures, by showing that it is possible to induce classification errors through tiny, almost imperceptible, perturbations. Vulnerability to such "adversarial attacks", or "adversarial examples", has been conjectured to be due to the excessive linearity of deep networks. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3
2
2

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 6 publications
1
17
0
Order By: Relevance
“…Previous studies have investigated the effectiveness of using sparsity as a defense against such adversarial perturbations. For example, Z. Marzi et al [5] shows that enforcing sparsity by taking the K out of N largest elements in magnitude, and zeroing the rest, for an inputted classifier sample in the wavelet domain, successfully decreases the misclassification caused by an adversarial attack on a Support Vector Machine (SVM). Furthermore, A. N. Bhagoji et al [6] shows that projecting high dimensional data onto a lower dimensional subspace using Principle Component Analysis (PCA) is effective in decreasing adversarial success.…”
Section: A Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have investigated the effectiveness of using sparsity as a defense against such adversarial perturbations. For example, Z. Marzi et al [5] shows that enforcing sparsity by taking the K out of N largest elements in magnitude, and zeroing the rest, for an inputted classifier sample in the wavelet domain, successfully decreases the misclassification caused by an adversarial attack on a Support Vector Machine (SVM). Furthermore, A. N. Bhagoji et al [6] shows that projecting high dimensional data onto a lower dimensional subspace using Principle Component Analysis (PCA) is effective in decreasing adversarial success.…”
Section: A Related Workmentioning
confidence: 99%
“…More specifically, the injection of visually imperceptible l 2 and l ∞ bounded perturbations into the input testing data has shown to render even the most robust classifiers useless. For example, both Support Vector Machines (SVMs) and Artificial Neural Networks with robust classification metrics have resulted in nearly 0% accuracy when processing perturbed data [5] [6]. This paper presents novel defense strategies, which are not only capable of combatting such adversarial attacks, but are also more robust than current standards in the literature.…”
Section: Introductionmentioning
confidence: 99%
“…Although we do not provide decision-based attack results, other empirical work suggests that robustness in this regime can be improved with population nonlinearities, sparsity, and recurrence. For example, robustness to decision-based attacks has been shown by imposing sparsification ( Marzi, Gopalakrishnan, Madhow, & Pedarsani, 2018 ; Alexos, Panousis, & Chatzis, 2020 ), recurrence ( Krotov & Hopfield, 2018 ; Yan et al, 2019 ), and specifically with the LCA network ( Springer, Strauss, Thresher, Kim, & Kenyon, 2018 ; Kim, Yarnall, Shah, & Kenyon, 2019 ; Kim, Rego, Watkins, & Kenyon, 2020 ). We offer a theoretical explanation for these findings.…”
Section: Discussionmentioning
confidence: 99%
“…In [41] it was observed that, if the input dimension is huge, even tiny perturbations, distinguishing an original from an adversarial image, can accumulate into an inner product with a weight vector to produce a huge distortion which sets the DNN astray onto a wrong classification. Subsequently, work in [70,71] proposes to combat such dimensionality phenomenon with a sparsifying front end which projects the input towards a lower dimensional space. Alternatively, [72] incorporates a subnetwork trained to distinguish legitimate from adversarial images.…”
Section: Related Workmentioning
confidence: 99%